Gastroprotective Effects of Ethanolic Leaf Extract of Abelmoschus esculentus on Phenylhydrazine-Induced Gastric Toxicity in Wistar Rats - Elizabeth Obioma Nweke; Benedict Onyekachukwu Ekwuno; A. U. Obi; Tochukwu Miracle Nweke (IPS Journal of Basic and Clinical Medicine, 2026)
Phenylhydrazine is a hydrazine derivative widely used experimentally to induce oxidative and haemolytic tissue injury in animal models. This study investigated the ameliorative effect of ethanolic extract of okra (Abelmoschus esculentus) leaves on phenylhydrazine-induced gastric toxicity in adult male Wistar rats. Twenty-five adult male Wistar rats (140-220 g) were randomly assigned into five groups of five animals each. Group A (control) received feed and distilled water ad libitum; Group B received phenylhydrazine only (40 mg/kg); Group C received ethanolic extract of A. esculentus only (100 mg/kg); Group D received phenylhydrazine (40 mg/kg) co-administered with the extract (100 mg/kg); and Group E received phenylhydrazine (40 mg/kg) co-administered with a higher dose of the extract (200 mg/kg). Administration was carried out daily by oral cannula for 21 days. Body weight, relative stomach weight, and gastric histoarchitecture were assessed at the end of the study. The median lethal dose (LD50) of the extract, determined by Lorke's method, exceeded 5000 mg/kg, indicating a wide margin of safety. Rats induced with phenylhydrazine alone (Group B) showed a non-significant reduction in body weight and relative stomach weight, alongside severe histological gastric ulceration with marked inflammatory cell infiltration of the submucosa. Co-administration of the extract with phenylhydrazine (Groups D and E) was associated with visibly reduced ulceration and progressively improved mucosal healing relative to Group B, with the higher extract dose (Group E) showing the more advanced histological recovery. These findings suggest that ethanolic extract of A. esculentus exerts a dose-related gastroprotective and ameliorative effect against phenylhydrazine-induced gastric injury, supporting its potential as a dietary adjunct in the management of oxidative gastric mucosal damage.